Analysis of the Effect of Position and Dimension of Infrared Burner on Heat Distribution and Efficiency of Butterfly Pea Flower Drying Oven - Febriana, Miftakhul Jannah; Rhakasywi, Damora; Fahrudin, Fahrudin (Journal La Multiapp, 2025)
Drying is a process of reducing the moisture content of materials using thermal energy. A drying oven equipped with infrared burner technology offers improved efficiency for drying butterfly pea flowers (Clitoria ternatea); however, uneven heat distribution remains a challenge. This unevenness can result in non-uniform drying, prolonged drying times, and reduced final product quality. This study employs Computational Fluid Dynamics (CFD) simulations to model the heat transfer process within the drying oven. Six different configurations of burner positions and dimensions were examined to evaluate their effects on heat distribution and drying rates. The results indicate that more uniform heat distribution is achieved with non-aligned burner positions, while larger burner sizes generally produce better heat distribution and faster drying rates. This research highlights the importance of optimizing burner position and dimensions to maximize drying efficiency and ensure consistent product quality.